Mindfulness, mental health, and motives for eating tasty foods when not in metabolic need - Moore, Katherine G.; Rice, Justess D.; Gampher, John E.; Boggiano, Mary M. (Frontiers in Psychology, 2024)
Habitual consumption of highly palatable foods when not in metabolic need (HPF-eating) is linked to obesity. High HPF consumption is also linked to mental health disorder (MHD) symptoms. Mindfulness-based interventions are popular treatments for obesity and MHDs, but little is known of the relationship between trait mindfulness and motive-based HPF-eating. Therefore, N=927 young adults completed a survey that included the Palatable Eating Motives Scale-7 (which identifies Coping-, Reward enhancement-, Social-, and Conformity-eating), the Mindful Attention Awareness Scale, Perceived Stress Scale, and demographic and BMI questions. An MHD questionnaire allowed comparison of HPF-eating between participants with and without various MHDs. Regressions revealed that Coping-eating was independently associated with lower mindfulness but also greater perceived stress, higher BMI, and female sex. Of these variables, only lower mindfulness was independently associated with Reward-, Social-, and Conformity-eating. Coping- and Reward-eating were more frequent in participants with vs. without an anxiety disorder, depression, ADD/ADHD, and PTSD. Coping-eating was also more frequent in participants with body dysmorphic disorder. These findings warrant investigations in participants with clinically-validated diagnoses for DSM-specific MHDs. Results from such investigations and the uncovered nature of associations between motive-specific HPF-eating and trait mindfulness could provide novel targets to improve mindfulness-based interventions for obesity and MHDs.